A Generalised Investigation of Adaptive Optimisation in the Chemical Processing of Minerals (The Australasian Institute of Mining and Metallurgy, 1985)
The strategy of adjusting operating conditions to maintain optimum process performance as the feed quality varies - adaptive optimisation - is being investigated by computer simulation of chemical processes for the treatment of ores. Those ore-process systems that are most likely to yield substantial benefits from adaptive optimisation are being identified as a guide to the selection and development of systems for practical application. The generalised mathematical representation of the cost structure, ore quality variations, process kinetics, reactor characteristics and operating variables for ore-process systems is described. Results are summarised for temperature, reagent concentration or residence time as the manipulated variable. For almost all systems, adaptive optimisation was economically beneficial, although a few exceptions have been identified where there is a significant synergistic effect between poor-performance and good-performance materials in a blended feed. The sensitivity of the benefits of adaptive optimisation to a range of economic and technical factors is summarised.